Guiliano Bugialli: Foods of Tuscany - D., J.M. (Petits Propos Culinaires, 1993)
Guiliano Bugialli: Foods of Tuscany: Stewart Tabori & Chang, New York, 1992: 298 pp, color photography by John Dominis, index, £25.00 in the UK.